A prevalence and psychometric study on fear of cancer in women with abnormal cervical cytology undergoing colposcopy. Issue 11 (28th August 2020) - Uner, Fatma Ozlem; Korukcu, Oznur
Abstract: Objective: To determine the levels of fear of cancer in women who were referred for colposcopy and to determine validity and reliability of the Cancer Worry Scale (CWS) in gynaecology patients. Methods: The study was conducted between March‐November 2017 with 200 women at the Gynaecologic Oncology Clinic at Akdeniz University Hospital in Turkey. Reliability analysis, confirmatory factor analyzes, and multidimensional sum‐score estimation were used for psychometric analyzes. One‐way ANOVA and independent samples t ‐test were also used. Results: Total score for the CWS of the participants was determined as 20.05 ± 7.87 in colposcopy patients. Marital status, information about the Papanicolaou (Pap) smear test and colposcopy, and fear of colposcopy were strongly associated with fear of cancer. We determined that a one‐factor structure emerged for the scale and that the total contribution of this factor to the explained variance was 53.35%. CFA was applied to obtain additional evidence of structural validity in line with the scores obtained from the scale. The overall Cronbach's alpha coefficient of the scale was 0.87. Conclusions: Our study revealed that levels of fear of cancer were high in women who were referred for colposcopy. Furthermore, the CWS was determined as a valid and reliable tool to measure the fear of cancer in women undergoing cervical screening/follow‐up for abnormal cytology.